PERLINDUNGAN HUKUM TERHADAP PEREMPUAN AKIBAT PERKAWINAN YANG DIBATALKAN - I Nyoman Wirayusa; A.A Gde Putra Arjawa; Kadek Dedy Suryana (Yayasan Nusantara Hasana Berdikari, 2024)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the belief in the Almighty God. The implementation of marriage must be based on feelings of affection and love, so both agree to determine a potential life partner to move up to a more sacred level, namely marriage. Therefore, marriage must fulfill the requirements and pillars of marriage determined by religion. The main issues that will be discussed are 1. How do you carry out a legal marriage according to the Marriage Law? 2. What is the legal protection for women whose marriages are annulled? The type of research carried out is normative research which is supported by a statutory approach, normative analysis which shows that the validity of marriage is based on legal principles, applicable legal norms, while the research analysis is conceptual which concerns the concept of marriage. Based on the results of the discussion, a marriage must be carried out according to religious law and then registered at the civil registry office, as regulated in Article 2 paragraphs (1) and (2) of the Marriage Law. In reality, it is religion that has an important role in proving whether a marriage is valid or not, because religion has sacred power which we will then be accountable for before God Almighty, after it is valid according to religious law then it will be registered at the civil registry office. Legal protection for women whose marriages are annulled, the woman can file a lawsuit with the religious court to obtain material or formal rights over the annulment of a marriage.